Analisis Keamanan Sistem Pembayaran Digital terhadap Perlindungan Data Pengguna - Nova, Nabilla Ivana; Nabila, Sela; Paiza, Parid Rehan; Sinaga, Norita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing adoption of digital payment systems has significantly transformed transaction patterns by offering faster, more practical, and efficient payment processes. These systems also play an important role in promoting financial inclusion and supporting economic recovery. Nevertheless, the growing reliance on digital payments presents various data security risks that may harm both users and service providers, including personal data breaches, identity theft, social engineering–based fraud, and account takeover incidents. This study aims to analyze the security mechanisms implemented in digital payment systems and to examine user data protection practices adopted by service providers in Indonesia. The research uses a qualitative approach through literature review and descriptive analysis of scientific journals, digital financial industry reports, technology whitepapers, and national data protection regulations. This method enables the identification of existing technical practices, governance policies, and security gaps. The findings show that most service providers have implemented essential security measures, such as end-to-end encryption, Transport Layer Security (TLS) protocols, server-side data encryption, tokenization of card data, multi-factor authentication, and one-time password (OTP) verification. Many platforms also integrate machine learning–based systems to detect suspicious activities and prevent fraud proactively. However, human factors and governance weaknesses remain key vulnerabilities. Limited digital security literacy among users increases exposure to phishing and credential misuse, while weak internal controls, inadequate incident management, and low transparency regarding data handling heighten risks. Therefore, strengthening technology, governance, and user education is crucial to ensuring a secure and sustainable digital payment ecosystem.